Research on Surrounding Rock Deformation and Mining Field Stress Distribution during Gob-Side Entry Retaining by Roof Cutting and Pressure Releasing in the Inclined Thick Coal Seam - Man Sun; Kengkeng Ye; Pengfei Guo; Zhupeng Jin; Yan Sun; Hongda Liang (Advances in Civil Engineering)
In recent years, the technology of the gob-side entry retaining by roof cutting and pressure releasing (GERRC) has been widely used in coal mining. However, the stability of the roadway surrounding rock structure during GERRC in the coal seam with high dip angles is a major concern, limiting the widespread application of this technology. In this study, we analyzed the deformation and stress evolution of roadway surrounding rock during GERRC in the 011810-working face of Jinfeng Coal Mine using theoretical analysis and numerical simulation. The results show that in coal seams with high dip angles, the gangue in the gob will slide down the lower trough, providing enough support for the upper rock layer and limiting rotation deformation along the gob-side entry roof during GERRC. This weakens the impact of mining pressure on the roadway and promotes the stability of the surrounding rock structure. However, the stress in the coal of the lower roadway in the advanced influence area is the largest, reaching 16.3 MPa due to the influence of buried depth. The stress of the surrounding rock of the gob-side entry tends to be stable at 110 m behind the working face in the lower roadways. There is also an obvious pressure relief zone in the coal in front of the working face, 10 m away from the cutting line, during GERRC. Its maximum stress is only 61.3% of the advanced coal and 10.0 MPa, indicating that the pressure relief effect of the roof cutting on the inclined coal seam is significant.